2021
DOI: 10.1111/vde.13026
|View full text |Cite
|
Sign up to set email alerts
|

Transient and reversible reduction of stratum corneum filaggrin degradation products after allergen challenge in experimentally mite‐sensitised atopic dogs

Abstract: Background -A defective skin barrier occurs in dogs with atopic dermatitis, and there is controversy over whether this defect pre-exists, or is secondary to allergic inflammation.Objectives -To study if an allergen challenge decreases the natural moisturising factor (NMF), which contains the main filaggrin degradation products.Animals -Four house dust mite (HDM)-sensitised adult atopic dogs from a research colony.Methods and materials -Dogs were challenged epicutaneously with HDMs on the right lateral abdomen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It is still unknown if the demonstrated alterations of these proteins, enzymes and NMFs represent a primary defect or are secondary to an inflammatory state. A very recent study, using experimentally sensitised atopic dogs, 21 indirectly suggested that some of these alterations may be a result of cutaneous allergic inflammation rather than being a primary defect.…”
Section: Updates On Stratum Corneum Structural Proteinsmentioning
confidence: 99%
“…It is still unknown if the demonstrated alterations of these proteins, enzymes and NMFs represent a primary defect or are secondary to an inflammatory state. A very recent study, using experimentally sensitised atopic dogs, 21 indirectly suggested that some of these alterations may be a result of cutaneous allergic inflammation rather than being a primary defect.…”
Section: Updates On Stratum Corneum Structural Proteinsmentioning
confidence: 99%
“…Skin barrier dysfunction and abnormalities in keratinocyte differentiation appear to play an important role in canine atopic dermatitis (AD) [ 1 , 2 , 3 ]. Debate exists as to whether some of these changes are primary and linked to genetic mutations [ 4 , 5 ] or whether they are mainly observed due to inflammation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main targets of the multimodal approach to CAD management is restoring epidermal barrier function and integrity [ 4 ]. Although it is still not clear whether the defective skin barrier is pre-existing or is secondary to allergic inflammation, it has been suggested that some of the skin barrier anomalies may develop secondary to the underlying skin inflammation [ 9 ]. Lipid alterations have been reported in CAD with decreased levels of free fatty acid and ceramides in the stratum corneum (SC) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%